THE RAIL STATE OF THE APPLICATION OF TRANSFORMATIONAL LEADERSHIP AMONG SECONDARY SCHOOL LEADERS IN THE STATE OF KHARTOUM - Hussen, Bannaga Taha Al-Zubair (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The study aimed to identify the reality of the application of transformational leadership among secondary school leaders from the teachers' points of view. In this study, the researcher followed the descriptive analytical approach; The study population included (323) teachers. The researcher chose a simple random sample of (168) teachers. The researcher also used the questionnaire as a tool to collect data: to analyze the data, the researcher used the statistical analysis program, the Statistical Package for Social Sciences (SPSS). The findings showed that there is  highly effect, with an arithmetic mean of 3.92, In light of these results, the study recommended a set of recommendations, the most important of which are: more dissemination of the culture of transformational leadership, setting accurate criteria by the Educational Department to select leaders, and holding specialized training courses with the aim of increasing the degree of awareness among school leaders of the importance of applying the dimensions of transformational leadership.